Optimización de la farmacoterapia a pacientes con hipertensión arterial del “Hospital San Juan de Lurigancho” - Aparcana Ataurima, Isabel M. (2022)
High blood pressure is a chronic disease that is increasing worldwide and in Perú; so that patients suffering from this disease may have drug-related problems. The objective of this research was to evaluate if pharmaceutic intervention (FI) optimizes the pharmacotherapy of patients with high blood pressure (HBP). The type of study was prospective, descriptive and longitudinal. The Dáder method was used to carry out the pharmacotherapeutic follow-up (PFU), the Morisky- Green test and the Battle test to evaluate compliance and knowledge; patients with arterial hypertension were evaluated, who were treated at the San Juan de Lurigancho Hospital for five months. The study included 13 patients with an initial mean blood pressure value of 151/95.62 mmHg, reducing after the intervention to 140.30/88.9 mmHg (p<0.05), in the same way, therapeutic compliance had an initial value of 15.38% and increased 69.23% (p<0.05) at the end of the PFU, and the percentage of patients with knowledge at the beginning was 38.46 % and at the end of the PFU it was 92.31 % (p<0.05). In total, 25 drug-related problems (DRPs) were detected, of which were reduced after the interventions to 5 DRPs, demonstrating the degree of acceptance of FI to prevent and resolve DRPs. It was concluded that the optimization of pharmacotherapy is positively influenced by the pharmaceutical intervention in the PFU, improving the patient´s health status.